Bimbingan Konseling Islam untuk Mengatasi Depresi di Hospital Bintulu Malaysia - Ahmad Samerin bin Abu Bakar (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2019)
This study aims to determine the methods and techniques in Islamic counseling guidance services to overcome depression in the early adult phase, find out the material and media that are used in Islamic counseling guidance services to overcome depression in the early adult phase, find out the results achieved from Islamic counseling guidance services to overcome depression Early adult phase at Bintulu Hospital, Sarawak, Malaysia. This research uses descriptive qualitative method, with data collection techniques in the form of observation, interviews, and literature study. The results showed that the methods and techniques used in this counseling guidance service were to provide direct guidance individually with personal conversation techniques such as dialogue sessions between two parties about patient psychology issues. The material in Islamic counseling guidance services provided to patients to overcome depression. Islamic Counseling Guidance Services provide positive changes in patients at Bintulu Hospital. Counseling guidance services will be more effective when done with an individual approach and know the client's background.Penelitian ini bertujuan untuk mengetahui metode dan teknik dalam layanan bimbingan konseling Islami untuk mengatasi depresi fase dewasa awal, materi dan media yag digunakan dalam layanan bimbingan konseling Islami untuk mengatasi depresi  fase dewasa awal, mengetahui hasil yang dicapai dari layanan bimbingan konseling untuk mengatasi depresi  fase dewasa awal. Penelitian ini menggunakan metode deskriptif kualitatif, dengan teknik pengumpulan data observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukan bahwa, metode dan teknik yang digunakan dalam layanan bimbingan konseling  ini adalah dengan memberikan bimbingan langsung secara individual dengan teknik percakapan pribadi seperti sesi dialog antar dua pihak tentang permasalahan psikologi pasien. Memberikan materi dalam layanan bimbingan konseling Islam yang diberikan kepada pasien untuk mengatasi depresi. Layanan Bimbingan Konseling Islam memberikan hasil perubahan positif pada diri para pasien. Layanan bimbingan konseling lebih efektif dialkukan dengan pendekatan individuan dan mengetahui latar belakang pasien.